Comparison of different feedstocks for biodiesel production - Shukla S.K.; Verma S. (My University, 2025)
Biodiesel is a good alternative fuel, owing to its renewability and comparatively far less pollution than conventional fuel. It is important to produce biodiesel at nominal cost to make it viable for industrial as well as transportation applications. In this chapter the technical and economical aspects of various biodiesel production methods, such as the conventional mechanical stirring method for biodiesel production with different catalysts (e.g., homogeneous basic catalysts, homogeneous acid catalysts, two-step catalysis method, heterogeneous catalysts, enzymatic catalysts) and a nonconventional ultrasonic cavitation method, are reviewed. A parametric study has also been done to show the effects of various parameters (e.g., feedstock, catalyst) on the production of biodiesel by these methods. It is inferred that process integration, large plant production capacities, cost of raw materials, and optimized reaction conditions have major impacts on the economy of any biodiesel production method. The study also revealed that better economic data using optimization of above parameters can be obtained for biodiesel production at large scale. © 2023 Elsevier Inc. All rights reserved.